Which term completes the product so that it is the difference of squares?
(-5x-3)(-5x+
-9
-3
Mark this and return
Save and Exit
Sub

Respuesta :

Answer:

the answer is  3

Step-by-step explanation:

(-5x-3)(-5x+3)=(5x)^2 - (3)^2

A difference of squares is the difference of two squared terms.

We have

a^2 - b^2

We can factorize the difference of squared terms like this:

a^2-b^2 = (a+b)(a-b)

We have (-5x-3)(-5x+3)

Lets prove it:

(-5x-3)(-5x+3) = (-5x*-5x)+(-5x*3)+(-3*-5x)+(-3*3)

(-5x-3)(-5x+3) = 25x^2+(-15x)+(15x)+(-9)

(-5x-3)(-5x+3) = 25x^2-15x+15x-9

(-5x-3)(-5x+3) = 25x^2-9

(-5x-3)(-5x+3) = (5x)^2 - (3)^2

ACCESS MORE